Second-order spectral lineshapes from charged interfaces - Paul E. Ohno; Hong-fei Wang; Franz M. Geiger (Nature Communications, 2017)
Charged interfaces are important in chemical systems, but the influence of charge on vibrational sum frequency spectra has only recently been considered. Here the authors show the importance of accounting for the interfacial potential-dependent χ(3) term in interpreting spectral lineshapes from charged interfaces.